The role of trust in shaping urban planning in local communities: The case of Hammarkullen, Sweden - Hansson Stina (Bulletin of Geography. Socio-Economic Series)
Urban planning is increasingly focusing on the social aspect of sustainability. The 2014 report Differences in Living Conditions and Health in Gothenburg shows important and increasing inequalities between different parts of the city, a development seen in cities across the world. The city of Gothenburg has set as its goal the decrease in inequalities by joining forces with civil society, the private sector, academia and people living in the city. Participation and inclusion become important tools in city planning processes for the authorities to understand local conditions, particularly to understand the living conditions of people in socio-economically marginalised areas, whose voices are rarely listened to, and to enable their active participation in shaping outcomes. In this article, we explore the role of trust in improving urban planning, and in shaping possibilities for participation that is positively experienced, in the sense that it increases people’s sense of control over their neighbourhoods. Based on empirical work in Hammarkullen, a socio-economically marginalised area in Gothenburg, the article shows how specific local configurations of trust have an impact on local development plans. It further shows how participatory practices coarticulate with the local social situation to shape outcomes in a certain way. Grounded in the empirical study, the paper argues for the importance of understanding the local conditions of trust and how they interact with planning processes in shaping outcomes and future possibilities of cooperation. Further, the paper argues for the need to take the local conditions of trust into account early in the planning phase.